Coplanar Qca Adders for Arithmetic Circuits - Safoev, Nuriddin; Cheol Jeon, Jun (International Journal of Engineering and Technology, 2018)
A quantum-dot cellular automaton (QCA) is one of the most perspective nanotechnologies for future computing paradigm. We propose low complexity QCA adders for arithmetic circuit design. The proposed majority-gate based full adder is coplanar layout, and on the basis of clock-phase crossover technique. The results of the proposed structures from the QCA simulator tool are analyzed and compared with previous works.Â Â